Pendampingan Pemasaran Digital Pada UMKM Konveksi Aura Desa Kayen Lor Kecamatan Plemahan Kabupaten Kediri - Nugraha, Bagas Barlaian; Khasanah, Devi Umrotin; Rafif, Moch.; Fadilah, Rika Alip Nur; Azizah, Ristia (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The purpose of this community service program is to provide digital marketing assistance to MSME employees in Kediri Regency, specifically the Aura Convection, and ensure business continuity. This activity is able to increase sales and profits, expand the target market, deepen customer loyalty, and increase competitive advantage. The benefits derived from this activity are for participants to gain knowledge and expertise in digital marketing, with the aim of increasing product production and promotion activities. Increased product orders from a wider target market will also be received. The method used is participatory action research (PAR). The results of the dedication can be concluded that digital marketing is carried out so that Aura Convection consumers increase and expand from various regions. This digital marketing assistance uses Instagram media, which will be filled with video content and Aura Convection products. This video content is in the form of product manufacturing procedures, types of products produced, and convection profiles. Video content published on the Aura Convection Instagram account.